سبب مرض الطاعون وطرق الاحتراز منه: دراسة مقارنة في ضوء الأحاديث النبوية والطب المعاصر: The Cause of the Plague and Its Prevention: A Comparative Study Based on the Prophet's Hadiths and Modern Medicine - Mohd Hamdan, Muhammad Akmalludin; Ismail, Mohd Yusuf (Maʿālim al-Qurʾān wa al-Sunnah, 2021)
This paper is concerned with the cause of the plague and its prevention. It aims to investigate the prophetic guidance on this issue compared to medical discoveries of the modern era. The importance of this research lies in multiple prophetic hadiths regarding the plague disease and its accordance with the continuity of research and recent findings in contemporary medicine. The researcher followed two approaches in this study, namely analytical and comparative approaches. In the first part, the researcher defined the plague and its difference with pestilence. In the second part, the researcher compared the prophetic guidance and contemporary medical findings regarding plague definition, the cause of its occurrence, and ways to guard against it. The paper shows agreements between the hadiths of the Prophet and contemporary medicine in this issue. In a way, modern medicine expands on matters clarified by the hadiths in some respects.